Building Moderation in Islamic Education: Curriculum Perspectives and Model Development - Makinuddin, Mohammad; Shobri, Khoirus (Journal of Education and Religious Studies, 2024)
This research aims to examine the concept of moderation (wasathiyah) in Islamic education, identify the challenges in its implementation, and explore strategies to strengthen a moderate curriculum across various educational institutions. A qualitative research approach was employed, utilizing literature study techniques and content analysis of academic literature, books, and relevant documents related to Islamic education and moderation. The study found that moderate Islamic education emphasizes a balance between the textual and contextual understanding of Islamic teachings, promoting values such as tolerance, justice, and openness. Implementation of moderation in the curriculum is achieved through integrating universal human values, adopting contextual learning approaches, and enhancing educator competence. Key challenges include the influence of exclusive ideologies, curriculum limitations, and negative impacts of social media. Addressing these challenges requires comprehensive strategies such as educator training, digital literacy programs, and collaboration among government, educational institutions, and communities. As a qualitative literature-based study, the findings are limited by the availability and scope of existing academic sources. Further empirical research involving field studies and stakeholder interviews is recommended to validate and expand upon these insights. This research contributes to the discourse on Islamic education by highlighting the critical role of moderation in curriculum development. It offers practical recommendations for policymakers and educators to foster a generation of Muslims who are tolerant, inclusive, and capable of thriving in pluralistic societies, thereby supporting the construction of a peaceful and just civilization..